Childhoods at the intersection of the local and the global - Twum-Danso Imoh, Afua; Ame, Robert (Palgrave Macmillan, 2020)
Childhoods at the Intersection of the Local and the Global examines the imposition of the modern Western notion of childhood, which is now deemed as universal, on other cultures and explores how local communities react to these impositions in various ways such as manipulation, outright rejection and acceptance. The book discusses childhoods in different regions of the world and boasts a range of contributors from several academic disciplines such as Sociology, Social Work, Education, Anthropology, Criminology and Human Rights, who are experts on the regions they discuss. The book argues against the notion of a universal childhood and illustrates that different societies around the world have different notions of childhood. This book is recommended reading for students, scholars and practitioners working with children in the Global South as well as internationally